Melampaui batas kelas: Rahasia belajar bahasa arab gen Z di era digital - Hotimah, Khusnul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze Arabic language learning approaches that align with the characteristics of Generation Z in the context of online education. Generation Z is known as a digital-native generation with learning preferences that emphasize technology, visual engagement, collaboration, and interactive methods. Unfortunately, Arabic language instruction has largely relied on conventional approaches that do not align with Gen Z’s learning style, such as one-way lectures and monotonous memorization. This research employs a qualitative method with a library research approach, reviewing various relevant literature related to Gen Z characteristics, digital learning strategies, and innovations in Arabic language teaching. The findings show that integrating technology through gamification, online learning applications, and educational social media content can be effective solutions to increase Gen Z’s interest and comprehension in Arabic. Furthermore, Arabic should be introduced not only as a religious subject but also as a life skill with global competitiveness. Through contextual, enjoyable, and meaningful approaches, Arabic learning can become more inclusive and adaptive to the needs of today’s generation.